Production of sustainable bio-jet fuel via single-step deoxygenation of palm-based feedstock / Elaine Why Siew Kuan - Elaine Why , Siew Kuan (2022)
The development of bio-jet fuel helps to sustain the demand of air transportation, and reduces the dependency on fossil fuel. According to literature, parameters such as type of catalyst, fatty acid profile of feedstock and blending ratio with Jet A-1 fuel, will affect the final hydrocarbon composition and characteristics of the overall fuel. This work aims to produce bio-jet fuel from palm-based oils via deoxygenation process. The product yield and selectivity of the bio-jet fuel were investigated based on different types of commercial catalysts (e.g., CaO, Zeolite, V2O5, Pd/C and TiO2), as well as catalyst loading and different types of palm oil-based feedstock (e.g., waste cooking oil, palm olein, palm kernel oil). Besides, fuel characteristics of different palm-based bio-jet fuel and its blending ratio of bio-jet fuel in Jet A-1 fuel were further tested. The catalyst reusability and soot particle emission characteristics of the fuel were studied as well, by investigating their morphologies and particle size distribution respectively. The deoxygenation of palm kernel oil by catalytic cracking with Pd/C catalyst at 8 wt% were found to be the most favorable pair of feedstock and catalyst (i.e., ~96% yield of liquid product, ~73% jet paraffin selectivity). Besides, the blending study indicated that 20 vol% of palm kernel oil-derived bio-jet fuel blended in Jet A-1 fuel was concluded as the most promising ratio. This is because it exhibited the most favorable low temperature fluidity, by having good amount of isoparaffin to lower the tendency of crystallization process during low temperature. Besides, it also showed good chemical properties, due to fair amount of oxygenates and aromatics. Thus, oxidation and soot emission were hindered during fuel combustion. Although Pd/C-derived bio-jet fuel blend exhibited better fuel properties, V2O5 catalyst is concluded to have better reusability than Pd/C catalyst.